Academic Performance and Resilience in Secondary Education Students - Ana María Carroza-Pacheco; Benito León-del-Barco; Carolina Bringas Molleda (Journal of Intelligence)
Academic performance is a factor of concern and interest in the educational context for the improvement of the educational and economic system of any country. Determining the factors influencing it has been the subject of multiple investigations. This study focused on analysing which dimensions of school resilience could act as determinants of academic performance in a sample of 609 Spanish secondary education students, aged between 11 and 17 years. The School Resilience Scale (SRS) was used as a data collection instrument. The data were analysed using analysis of variance and discriminant analysis based on a canonical function model, which suggested the existence of a direct and significant relationship between academic performance and all dimensions of resilience, with somewhat larger effect sizes for the Internal Resources and Identity–Self-Esteem dimensions, which allowed us to classify students with particularly high levels of performance. The results also show that the school year was significantly associated with academic performance, with the highest percentages of students at the highest level observed in the 2nd and 3rd years.